2022
DOI: 10.1051/0004-6361/202142138
|View full text |Cite
|
Sign up to set email alerts
|

J1721+8842: a gravitationally lensed binary quasar with a proximate damped Lyman-α absorber

Abstract: High-redshift binary quasars provide key insights into mergers and quasar activity, and are useful tools for probing the spatial kinematics and chemistry of galaxies along the line of sight. However, only three sub-10-kpc binaries have been confirmed above z = 1. Gravitational lensing would provide a way to easily resolve such binaries, study them in higher resolution, and provide more sightlines, though the required alignment with a massive foreground galaxy is rare. Through image deconvolution of StanCam Nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…The system was originally discovered by Lemon et al (2019) who confirmed the source to be at z≈2.37, with strong absorption features. Gaia DR2 catalogues 5 detections, and an in-depth study of this system by Lemon et al (2022) show that there are two quasar sources at similar redshifts, with one being lensed into four images, and one into two images. They provide several mass models for the system, which we will compare to in Section 4.2.…”
Section: J1721+8842mentioning
confidence: 92%
See 1 more Smart Citation
“…The system was originally discovered by Lemon et al (2019) who confirmed the source to be at z≈2.37, with strong absorption features. Gaia DR2 catalogues 5 detections, and an in-depth study of this system by Lemon et al (2022) show that there are two quasar sources at similar redshifts, with one being lensed into four images, and one into two images. They provide several mass models for the system, which we will compare to in Section 4.2.…”
Section: J1721+8842mentioning
confidence: 92%
“…For several systems, mass models based on ground-based imaging exist in the literature (e.g. Rusu & Lemon 2018;Lemon et al 2018Lemon et al , 2019Lemon et al , 2020Lemon et al , 2022. Given the difference in data resolution and depth, modeling approaches, treatment of perturbers, and parameterization it is difficult to perform a detailed quantitative comparison.…”
Section: Comparison To Published Mass Modelsmentioning
confidence: 99%
“…The 2D spectra were bias-subtracted and cosmic rays masked, and a model for the sky background based on the 5 either side of the object was subtracted. We extract separate spectra using a forward-modelling process, as described fully in Lemon et al (2022). Briefly, we forward model the quasar images as Moffat profiles onto a pixelised grid, and derive the 1D spatial spread function after applying a slit of 1 in width.…”
Section: Spectroscopic Follow-upmentioning
confidence: 99%
“…The main observational difficulty comes from insufficient resolution of the imaging surveys that limits the minimum sep-aration between the detected pairs of Active Galactic Nuclei (AGN) to a few kiloparsecs (see e.g. Tang et al 2021;Chen et al 2022a;Lemon et al 2022, for recent discoveries). The higher resolution of radio observations offers the possibility to detect closer pairs (Rodriguez et al 2006), but this technique remains limited to the nearest galaxies and to a minimal separation of ∼ 10 pc, leaving the sub-parsec separation SMBHBs undetected.…”
Section: Introductionmentioning
confidence: 99%